Monitoramento e desempenho de indicadores participativos em sistemas tradicionais de produção de erva-mate no Centro-Sul e no Vale do Iguaçu, Paraná, Brasil - Adriana Rita Sangalli; Ricardo Eduardo de Freitas Maia; Mirian Fabiane Strate; Evelyn Roberta Nimmo; André Eduardo Biscaia Lacerda; Tatiana Mota Miranda; Gabriela Coelho-de-Souza (Desenvolvimento e Meio Ambiente, 2022)
The traditional system of yerba mate production (STPEM) presents the Mixed Ombrophilous Forest of southerner Brazil, characterized as agroforestry systems, that roots are related to the management of the faxinal and caívas. Whereas the implicit complexity in the coverage of these systems, in environmental, economic, socials, and cultural dimensions, this survey lens to analyze the initial monitoring and the performance of these traditional systems of production, in municipalities of Paraná state, through the participative construction of indicators. The field research happened in two stages: the first, as of the monitoring of a workshop conducted in the city of União da Vitória, attended by farmers and representatives from several institutions related to the Yerba Mate Observatory, in partnership with the university researchers. In this event, through the collective construction of an accessible and utility indicators system by the handlers of STPEM, technical parameters were created linking the scientific knowledge to the farmers’ traditional knowledge. This process allows the measurement of the amplitude of the systems in their principal dimensions, enabling monitoring and monitoring over time, future comparisons related to the evolution of systems. The second stage refers to the application of these macro indicators in twelve families of rural properties located in four municipalities (Inácio Martins, Rebouças, Biturunaand São Mateus do Sul). Results demonstrate strengths and limitations in STPEM, highlighting that the monitored systems contribute effectively with the conservation of the Mixed Ombrophilous Forest, promoting benefits to properties and surroundings, as water issue emphasized by farmers surveyed. The indicator system realization, constructed with the social actors, opens an interlocution space with the public policies, considering local realities and needs, often only known by the farmers themselves and stimulating new research agendas.